How Do Anti-discrimination Laws Affect Firm Performance and Financial Policies? Evidence from the Post-World War II Period - Greene, Daniel; Shenoy, Jaideep (Management Science, 2022)
We exploit the staggered passage of state-level fair-employment laws in the post-World War II period to examine how stronger worker protection against racial discrimination affects firm profitability and financing decisions. We find that firms experience a decline in operating profitability after the passage of anti-discrimination laws. We also document that the adoption of these laws leads to a reduction in debt ratios, which suggests that firms are able to partially offset the negative effects on operating profitability by adjusting their capital structure. Consistent with theoretical predictions, these effects of anti-discrimination laws are more pronounced for firms in states and cities with a greater proportion of African Americans, firms with high labor intensity, firms in states experiencing high African American migration, and firms in concentrated industries. Some of our evidence suggests that anti-discrimination laws lead to a reduction in statistical discrimination or monopsony power rather than taste-based discrimination. Taken together, our results are supportive of theoretical models of discrimination and show that racial discrimination laws significantly affect firm operating performance and financial policies. This paper was accepted by David Simchi-Levi, finance.